IMPLEMENTATION OF THE CAMPUS TEACHING PROGRAM FOR GRADE 6 IN ACTIVITIES TO IMPROVE THE LITERACY AND NUMERATION OF CLASS 8 STUDENTS OF SMPBHINNEKA KARYA KLEGO 2023 - Istiana, azizah avika (Jurnal Pengabdian Melek Literasi, 2023)
The Teaching Campus Program is one of the Independent Campus Learning Programs(MBKM) from the Ministry of Education and Culture which empowers Indonesianstudents to be able to learn and contribute directly to the world of education, especiallyin developing the literacy and numeracy skills of students at the Junior High School(SMP) and The target schools for teaching campuses are in 3T areas (Disadvantaged,Frontier and Outermost). This program has been running in six classes, namely theprevious class, Teaching Campus Classes 1 to 5 and the current class, namely TeachingCampus Class 6 (KM6). Students who pass the selection in this program are assigned toschool partners selected by the organizers of the Teaching Campus program. The schoolwhere the Class 6 Teaching Campus program was implemented which the studentscarried out together with other fellow students is Bhinneka Karya Klego Middle School,Boyolali, Central Java. The programs that have been implemented by students during theassignment (4 months) are teaching programs, programs to help adapt technology, andprograms to help improve student literacy and numeracy. After carrying out the Class 6Teaching Campus assignment at Binneka Karya Klego Middle School from 14 August2023 to 02 November 2023, students and the school both received many benefits from thisprogram. Students gain a lot of direct experience in the field, both during learningactivities and also when preparing programs with colleagues from different campusesand majors. Meanwhile, the placement school admitted that it helped a lot by thepresence of students, both in the areas of teaching programs, helping with technologyadaptation, and helping to improve student literacy and numeracy.